2020
DOI: 10.1037/cbs0000178
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of laypeople’s perceptions of confession evidence and interrogation tactics.

Abstract: For a confession to be admitted as evidence, the confession must be voluntary, procured when a suspect is aware of his or her right to silence and counsel, and the methods that obtained the confession should not shock the conscience of the public. We conducted 3 studies on samples of Canadian citizens to begin to examine what the public does or does not find inappropriate in the context of police interrogations. Findings suggest that overtly coercive tactics are viewed as less appropriate than psychologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Despite the clear impact of minimization on sentencing expectations, surveys of laypeople suggest that they do not view minimization tactics particularly negatively. For instance, studies have shown that laypeople accept the use of some forms of minimization in police interviews (Homant & Witkowski, 2011;Moston & Fisher, 2007), that they do not view minimization as being overly coercive (kaplan et al, 2020), and that they do not recognize the risks of using implicit tactics against suspects (e.g., involuntary confessions; Blandón-Gitlin et al, 2011;Costanzo et al, 2010;Hall et al, 2020;Leo & Liu, 2009). Furthermore, research shows that when a suspect confesses, conviction rates increase even when the confession was elicited using coercive methods (e.g., minimization; Jones & Penrod, 2016kassin & Sukel, 1997;Wallace & kassin, 2012).…”
Section: Lay Perceptions Of Coercion In Police Interviewsmentioning
confidence: 99%
“…Despite the clear impact of minimization on sentencing expectations, surveys of laypeople suggest that they do not view minimization tactics particularly negatively. For instance, studies have shown that laypeople accept the use of some forms of minimization in police interviews (Homant & Witkowski, 2011;Moston & Fisher, 2007), that they do not view minimization as being overly coercive (kaplan et al, 2020), and that they do not recognize the risks of using implicit tactics against suspects (e.g., involuntary confessions; Blandón-Gitlin et al, 2011;Costanzo et al, 2010;Hall et al, 2020;Leo & Liu, 2009). Furthermore, research shows that when a suspect confesses, conviction rates increase even when the confession was elicited using coercive methods (e.g., minimization; Jones & Penrod, 2016kassin & Sukel, 1997;Wallace & kassin, 2012).…”
Section: Lay Perceptions Of Coercion In Police Interviewsmentioning
confidence: 99%